Fault Tolerance in Strongly Minimum Energy Topology with MLD: A Distributed, Energy Efficient yet Simple Protocol - Nunes, Ivan Oliveira; Vieira, Luiz Filipe M.; Loureiro, Antonio A. F. (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2015: Anais do XVI Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2015.22937, 2015)
Wireless Sensor Networks (WSN) have been the subject of extensive research due to their wide range of applications. A sensor node should have the longest lifetime possible, since we need to build a system that performs its functions effectively and, at the same time, spends the least amount of energy, allowing the battery to last longer. One of the functions that consumes more energy in a WSN is the wireless data transmission. In this context, it becomes interesting to determine a setting of transmission powers for the network sensor nodes so the network remains connected while nodes’ transmission powers remain minimum. The problem of minimizing the total energy consumption in a network is known in the literature as Strongly Minimum Energy Topology (SMET) and its decision version is known to be an NP-Complete problem. In this work, we evaluate the cost of adding fault tolerance through redundant paths to the SMET Minimum Spanning Tree (MST) topology, creating a redundant MST, a non-practical fault tolerant baseline algorithm. Next, we propose a practical redundant algorithm, Minimum Link Degree (MLD), which does not need any localization information and can be implemented in a distributed fashion. Our results show that the MLD topology is a promising approach, performing better than the redundant MST with respect to number of survived nodes’ faults.